2010
DOI: 10.4314/fje.v4i1.48003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Housing Satisfaction In Residential Localities Within Uyo, Nigeria

Abstract: In urban centers of most developing countries, one of the major problems is the assessment of the quality of residential neighborhoods. This has further compounded the problem of residential choice among urban dwellers. In Uyo, the Akwa Ibom State capital, the problem is magnified by the spatio-cultural patterns within the residential localities. By means of a survey of 20 of such localities using questionnaire, 1200 households were interviewed on housing and environment conditions expressed in 23 variables. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although several research studies (Ukoha and Beamish, 1997;Ilesanmi, 2005;Olatubara and Fatoye, 2007;Fatoye and Odusami, 2009;Jiboye, 2009Jiboye, , 2010 have evaluated public housing schemes in Nigeria with emphasis on residents' satisfaction and factors influencing it, no study has been done to assess the qualitative adequacy of housing provided in this programme, however, since the inception of the public housing programme in Ogun State. This is probably because the Federal Republic of Nigeria (1991) and Ikurekong (2009) indicated that the evaluation of housing programmes and assessment of the quality of residential neighbourhoods are key challenges in Nigeria. Hence, there is gap in literature on the qualitative adequacy of recently constructed public housing in this part of Nigeria, which the current study will attempt to fill.…”
Section: Introductionmentioning
confidence: 99%
“…Although several research studies (Ukoha and Beamish, 1997;Ilesanmi, 2005;Olatubara and Fatoye, 2007;Fatoye and Odusami, 2009;Jiboye, 2009Jiboye, , 2010 have evaluated public housing schemes in Nigeria with emphasis on residents' satisfaction and factors influencing it, no study has been done to assess the qualitative adequacy of housing provided in this programme, however, since the inception of the public housing programme in Ogun State. This is probably because the Federal Republic of Nigeria (1991) and Ikurekong (2009) indicated that the evaluation of housing programmes and assessment of the quality of residential neighbourhoods are key challenges in Nigeria. Hence, there is gap in literature on the qualitative adequacy of recently constructed public housing in this part of Nigeria, which the current study will attempt to fill.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers had been written though, relating to various individual indicators, consequences of housing satisfaction issues or at least with the user as focus. This category included the works of Ogu (2002), Oladapo (2006), andIkurekong (2009). While Ogu (2002) isolated the infrastructure component of the housing environment, Oladapo (2006) centred on maintenance awareness in the determination of user satisfaction.…”
Section: 20 Literature Reviewmentioning
confidence: 99%
“…While Ogu (2002) isolated the infrastructure component of the housing environment, Oladapo (2006) centred on maintenance awareness in the determination of user satisfaction. On his own, Ikurekong (2009) focused generally on determinants but ended shoring up infrastructure as the outcome. Others included the works of Jiboye (2009) and Jiboye (2010), both of which dwelt much on the systems approach of Onibokun (1974) but centred only on public housing.…”
Section: 20 Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation